СТИХОВИ ВИКТОРА ИГОА И ТУМАЧЕЊЕ ПРИПОВЕТКЕ ПУТ АЛИЈЕ ЂЕРЗЕЛЕЗА ИВЕ АНДРИЋА (Prilozi za književnost, jezik, istoriju i folklor, 2023)
The paper is dedicated to the analysis of Ivo Andrić’s novel The journey of Alija Đerzelez and its connection with the verses of Victor Hugo written by Ivo Andrić on the cover of the incomplete manuscript of the third part of the novel that is been kept in Archives of Serbian Academy of Science and Arts. Through analysis, we show that in this novel that has been printed for the first time complete, in Belgrade 1920, Ivo Andrić began to depict literary heroes who commit evil deeds, which was left aside in interpretations of this novel for a long time, since this layer of meaning remained in the shadows due to the effect of the grotesque and the presence of comedy. Alija Đerzelez is actually the first in a series of evil-doer in Andrić’s fictional worlds and the first literary hero on whom Andrić began writing about the influence of evil on human beings.